Geminivirus transmitidos por mosca blanca en Colombia - Morales, Francisco José; Muñoz, C.; Castaño Zapata, M.; Velasco, Ana Cecilia (2000)
Whitefly-transmitted geminiviruses are considered some of the most important pathogens of food and industrial crops in tropical and subtropical regions of the world, including most of the countries in Latin America. In Colombia, however, these viruses are not yet considered pathogens of economic importance for the agricultural sector. In this report, we describe the emergence of different geminiviruses transmitted by the whitefly Bemisia tabaci in various crops of socioeconomic importance, such as fruit crops, common bean, melon, soyabean and tobacco, in different regions of Colombia. We also show that wild plants may harbour geminiviruses capable of infecting cultivated plant species. Finally, we discuss some control measures to prevent the proliferation of B. tabaci and geminiviruses in food and industrial crops in Colombia. The geminiviruses detected in common bean are bean dwarf mosaic virus and bean golden yellow mosaic virus, described earlier in Colombia. The viruses found in giant granadilla [Passiflora mollissima], melon, soyabean and tobacco are new begomovirus species, tentatively named giant granadilla malformation virus, melon chlorosis virus, soyabean yellow mottle virus, and tobacco leaf crumple viruses, respectively.